Identification and Discrimination of Mycobacterium tuberculosis Complex with Traditional and Real-Time PCR in Different Specimens in Iraq - Ali, Shaymaa Mahmood; Al-Faham, Mohammad A.; Mankhi, Ahmed A. (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Tuberculosis (TB) is a major public health issue and a main cause of global morbidity and mortality. TB is the world’s ninth leading cause of death despite the numerous treatment strategies for managing the disease. Objective: To assess the traditional method (direct smear examination and culture) against real-time PCR as pulmonary and extrapulmonary tuberculosis laboratory diagnostic techniques. Cases and methods: Samples were collected from (612) TB cases, (409) of whom were pulmonary tuberculosis (PTB) and (203) were extrapolmonary tuberculosis (EPTB). The cases were seeking care at the Specialized Chest and Respiratory Disease Center/ National Reference Laboratory for Tuberculosis (NRL) in Baghdad, during the period 1st of May -1st of October 2019. Direct smear examination, Lowenstein-Jensen culture and Real Time PCR were used to diagnose TB. Results: Out of 612 samples received, 82(13.4%) were positive by smear microscopy, while 90(14.7%) were able to grow on Lowenstein-Jensen (LJ) media. Ninety DNA extracts from the samples which were positive on LJ media and 25 control specimens, were diagnosed with molecular analysis by using real time PCR to determine the species of Mycobacterium tuberculosis complex. The results revealed that the 71 samples (78.9%) were M. tuberculosis, three specimens (3.3%) were combined M. bovis and M. tuberculosis, and one M. tuberculosis, M. bovis, and M. bovis BCG, while15 (16.7%) were negative and subsequently excluded from study. Conclusion: The comparison between molecular diagnostic methods by using Real time PCR with conventional diagnostic methods, provides a new promising technique and is potentially a practical and rapid alternative to the slower traditional pulmonary and EPTB diagnostic culture. The results show M. bovis overall contribution on human TB in comparison to M. tuberculosis is minor among PTB and EPTB cases in the sample studied.